Effect of Goat Milk Yogurt for Prevention Hypercholesterolamic in Animal Model Rat (Rattus norvegius) Based on the Expression of Inducible Nitric Oxide Synthase (INOS) and a description of Liver Histopathology - Chanif Mahdi; Sukarno Hariyanto; Masdiana C. Pandaga (Indonesian Journal of Cancer Chemoprevention, 2016)
The pattern of high consumption of fat can lead to hypercholesterolemia were accompanied by increased levels of LDL which resulted in LDL oxidation, accompanied by an inflammatory reaction that can lead to liver tissue damage resulting in increased expression of inducible Nitric Oxide Synthase (INOS) and changes in liver histopathology. The purpose of this study was to investigate the influence of goat milk yogurt supplementation on the expression of INOS and liver histopathology picture. This study used 20 male rats, Wistar strain aged 10-12 weeks, weighing 150-200g. Giving goat milk yogurt for 42 days with a dose of 300mg/kg, 600mg/kg, and 900mg/kg and giving dietary hypercholesterolemia by administering poached quail egg yolk, lard, and cholic acid by the stomach sonde for 14 days. Parameters measured were the expression of INOS and liver histopathology picture. The analysis used in this study is the One Way Analysis Of Variance (ANOVA) followed by Tukey test 5%. The results showed that administration of goat milk yogurt as a precaution hypercholesterolemia at a dose of 300mg/kg, 600mg/kg and 900mg/kg give a highly significant effect (p <0.01) on the expression of INOS (p <0.01).The overall Result of each treatment were 0.47 ±0.03; 6.72 ± 0.11; 2.40 ±0.16;1.11 ±0.07and 0.66 ±0.19  Prevention with a dose of 900 mg/kg body weight is the most effective dose inhibits the expression of INOS.  Prevention with a dose of 900 mg/kg showed that the histopathological picture of approaching normal circumstances. The conclusion of the study is the provision of goat milk yogurt as a preventive action with a dose of 900 mg/kg of the most effective to inhibit the expression of INOS and maintain normal liver histology in rats given diets hypercholesterolemia.Keywords: Hypercholesterolemia, Expression of Inducible Nitric Oxide Synthase (INOS), goat's milk yogurt, liver histopathology